Edukasi Gizi Seimbang Dalam Pencegahan Dan Penanganan Stunting Di Desa Karang Dima Wilayah Kerja PKM Labuan Badas Labuan Sumbawa - Yunita Lestari; Has’ad Rahman Attamimi; Lina Etta Safitri (Compromise Journal Community Proffesional Service Journal, 2024)
Nutritional problems, especially stunting, cannot only be intervened in in the first thousand days of life (1000 HPK). Therefore, various efforts need to be made to prevent this nutritional problem from being overcome. One effort that can be made is nutritional education for parents and children in the community. This educational activity is part of community service activities which aim to increase the knowledge and attitudes of mothers and children in implementing the consumption of balanced nutritious food in children from an early age. This is an effort to prevent and overcome ongoing stunting at school age in the Working Area of ​​the Labuan Badas Community Health Center, Labuan Badas Village, Sumbawa. The intervention method used to achieve this goal was by holding interactive education using the counseling method which was carried out door to door for 39 participants.